PENGARUH PERMODALAN, RISIKO KREDIT DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA LPD SE-KECAMATAN GIANYAR TAHUN 2020-2022 - Dewa Gede Agung Aditya Putra; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2024)
Profitability is a description of a company's ability to generate net profit from activities carried out in a company's accounting period to generate profits and measure the level of operational efficiency and efficiency in using its assets. This study aims to determine the Effect of Capital, Credit Risk and Liquidity on Profitability at LPDs in Gianyar District in 2020-2022. The sample in this study was LPDs in Gianyar District, totaling 38 LPDs that were still active from 2020-2022, then the data used in this study was secondary data obtained from annual financial reports. Determination of the sample using the purposive sampling method with a total sample of 114 samples. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that Profitability has a significant positive effect on Profitability at LPDs in Gianyar District. Credit Risk has a significant negative effect on Profitability at LPDs in Gianyar District. Liquidity has a significant positive effect on Profitability at LPDs in Gianyar District.